Use of risperidone in-situ microparticles in real world: patterns of prescription and dose selection in patients with psychotic disorders - Ilaria Di Bernardo; Paolo Brambilla; D’Agostino Armando; Mauro Percudani; Giancarlo Cerveri; Giovanni Migliarese; Virginio Salvi; Annabella Di Giorgio; Valentina Dalò; Federica Calorio; Adelaide Panariello; Alessandro Galluzzo; et al. (International Clinical Psychopharmacology, 2026)
Long-acting injectable (LAI) antipsychotics are important for improving adherence and preventing relapse. Risperidone in-situ microparticles (ISM), a once monthly LAI using ISM technology, rapidly achieves therapeutic plasma levels without loading doses or oral supplementation. Real-world evidence on its use remains limited. This multicenter observational–naturalistic–retrospective study assessed prescribing patterns of risperidone-ISM across nine Public Mental Health Departments in Lombardy, Italy. Data from 218 inpatients and outpatients with psychotic disorders diagnosed according to diagnostic and statistical manual of mental disorders, fifth edition, text revision criteria were collected. Demographic, clinical, and pharmacological variables were analyzed. Patients were stratified by dose (75 vs. 100 mg), and group differences were assessed using χ 2 and analysis of variance tests. Multivariable logistic regression identified independent correlates of prescription of the 100 mg dose. Sample’s mean age was 41.8 years (69% male), with 71.1% receiving 100 mg. LAI initiation was primarily intended to improve adherence in 77.7% of cases. Among hospitalized patients, Brief Psychiatric Rating Scale scores decreased between admission and discharge (59.35 vs. 33.48); however, causality could not be inferred. The 100 mg group had significantly more male patients and showed higher rates of substance use and involuntary hospitalization, while the 75 mg group more often presented depressive symptoms and antidepressant use. In multivariable analysis, only involuntary hospitalization remained independently associated with receiving the 100 mg dose. This study provides real-world evidence on prescribing patterns of different risperidone-ISM doses and short-term clinical outcomes among treated patients.